Investigating the Relationships Between Structures and Properties of Al Alloys Incorporated With Ti and Mg Inclusions - SALMAN, SERDAR (ASME, 2016)
This study investigates the influence of titanium (Ti) and magnesium (Mg) additions on aluminum (Al) alloys in order to evaluate the relationship between the structure and properties of the new alloys. The alloys obtained at elevated temperatures mainly consist of Al-2Mg-1Ti, Al-2Mg-3Ti, Al-4Mg-2Ti, and Al-6Mg-2Ti alloys, as well as alpha and tau solid solution phases of intermetallic structures. Microstructural analyses were performed using X-ray diffraction (XRD), optical microscope, and energy dispersive spectrometry (EDS) techniques. Test results show that the average grain size of the alloys decreased with the addition of Ti inclusions during the casting and solidification processes, and the smallest grain size was found to be 90 mu m for the Al-6Mg-3Ti alloy. In addition, tensile properties of the Al-Mg-Ti alloys were initially improved and then worsened after the addition of higher concentrations of Ti. The highest tensile and hardness values of the alloys were Al-4Mg-2Ti (205 MPa) and Al-6Mg-3Ti (80 BHN). The primary reasons for having higher mechanical properties may be attributed to strengthening of the solid solution and refinement of the grain size and shape during the solidification process. For this study, the optimum concentrations of Ti and Mg added to the Al alloys were 4 and 2 wt.%, respectively. This study may be useful for field researchers to develop new classes of Al alloys for various industrial applications.
Keywords: Al alloys; Ti and Mg additions; casting; microstructures; mechanical properties; MECHANICAL-PROPERTIES; GRAIN-REFINEMENT; TENSILE PROPERTIES; MASTER ALLOYS; ALUMINUM; MICROSTRUCTURES; NUCLEATION; AL-5TI-1B; BEHAVIOR; ZN